2016
DOI: 10.1155/2016/5157930
|View full text |Cite
|
Sign up to set email alerts
|

Guy’s Stone Score (GSS) Based on Intravenous Pyelogram (IVP) Findings Predicting Upper Pole Access Percutaneous Nephrolithotomy (PCNL) Outcomes

Abstract: Objective. To predict the success rate and complications following percutaneous nephrolithotomy via the upper pole using the Guy's Stone Score (GSS) based on the findings of a preoperative intravenous pyelogram (IVP). Patients and Methods. Two hundred and twenty-seven renal operations, which were carried out using PCNL via the upper pole, were classified according to the GSS assigned. Any complications were classified according to the Clavien classification. The success rates and incidence of any complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…These results are similar to those of our study, as GSS-1 had the highest success rate of 87.4%, GSS-2 had 52.4%, GSS-3 had 48.4% and GSS-4 showed the lowest success rate of 4.3%. Clavien-Dindo classification in our study was also comparable to the Thailand study [ 37 ], as major complications (Clavien score of 1–2) were significantly higher in the cases with a higher GSS while minor complications (Clavien score of 3a-5) were significantly lower in patients with lower GSS. Tubeless PCNL entails a benefit over the standard PCNL in terms of shorter hospital stay and early recovery time in patients [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to those of our study, as GSS-1 had the highest success rate of 87.4%, GSS-2 had 52.4%, GSS-3 had 48.4% and GSS-4 showed the lowest success rate of 4.3%. Clavien-Dindo classification in our study was also comparable to the Thailand study [ 37 ], as major complications (Clavien score of 1–2) were significantly higher in the cases with a higher GSS while minor complications (Clavien score of 3a-5) were significantly lower in patients with lower GSS. Tubeless PCNL entails a benefit over the standard PCNL in terms of shorter hospital stay and early recovery time in patients [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…To predict the success rate and complications following PCNL, GSS is used. According to a study done in Thailand, the success rates were found to be 87.5% for GSS-1, 71.4% for GSS-2, 53.6% for GSS-3, and 38.5% for GSS-4 [ 37 ]. These results are similar to those of our study, as GSS-1 had the highest success rate of 87.4%, GSS-2 had 52.4%, GSS-3 had 48.4% and GSS-4 showed the lowest success rate of 4.3%.…”
Section: Discussionmentioning
confidence: 99%
“…A 20 Fr nephrostomy catheter was inserted and kept postoperatively till hematuria recovered. Postoperative chest x-ray was obtained in case of upper calyx access for the assessment of any pulmonary complications 5 . For the MM-PCNL group, the same procedure as S-PCNL was performed with some changes in tract dilatation and nephroscope.…”
Section: Methodsmentioning
confidence: 99%
“…When performing percutaneous nephrolithotomy (PCNL) to remove complex renal and upper ureteric stones from the upper pole of the kidney, the success rates and possible complications are assessed using Guy's Stone Score (GSS). Hence, GSS, based on IVP interpretation, is a reliable and simple tool for predicting the outcome, assisting in pre-operative planning, and counselling the patient [5].…”
Section: Intravenous Urography/intravenous Pyelographymentioning
confidence: 99%